Glycerol Acetylation Using Magnesium Fluoride Catalyst to Produced DAG and TAG - Qurrota A’yuni; Syafsir Akhlus; Harsasi Setyawati; Irmina Kris Murwani (IPTEK Journal of Proceedings Series, 2017)
Glycerol acetylation with acetic acid using magnesium fluoride catalyst have been investigated. Magnesium fluoride catalyst was prepared by sol-gel method with ethanol as gelating agent. The glycerol acetylation produced monoacetylglyceride (MAG), diacetylglyceride (DAG) and triacetylglyceride (TAG). The catalytic reaction carried out by thermal methods reflux under ambient conditions. The influence of reaction conditions such as the reaction time on the product distribution was investigated. The optimum of glycerol conversion was achieved at 5 hours of reaction time by 78.34% with selectivity of 30, 62 and 8% for MAG, DAG and TAG respectively. The reaction route over magnesium fluorides was observed by product as reactants, gradually. The results showed that the acetylation reaction of glycerol occurs via a parallel route to the first, followed by the consecutive route to produce DAG and TAG.